Bilateral mandibular buccal bifurcation cyst: A case report emphasizing the role of imaging examination in the diagnosis - Bautista, Cristhian Reynaldo Gomez [UNESP]; Milhan, Noala Vicensoto Moreira [UNESP]; Del Valle El Abras Ankha, Milagros [UNESP]; Do Prado, Renata Falchete [UNESP]; Cavalcante, Ana Sueli Rodrigues [UNESP]; De Castro Lopes, Sergio Lúcio Pereira [UNESP]; Anbinder, Ana Lia [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2019)
A mandibular buccal bifurcation cyst is an inflammatory cyst that usually occurs on the buccal aspect of the permanent mandibular first molar of children. This lesion is diagnosed by an association of radiographic, clinical, and histological features. We report a bilateral case of mandibular buccal bifurcation cyst and discuss the main findings of this entity. A 7-year-old girl presented pain and delayed dental eruption in the posterior mandibular region. A cone beam computed tomography was performed and revealed hypodense lesions involving the crown and root of the mandibular first molars, with expansion of the buccal cortical and lingual tilting of the molar roots. A biopsy was carried out, and the common features of an inflammatory odontogenic cyst were histologically observed. The final diagnosis was bilateral mandibular buccal bifurcation cyst. Clinicians need to be aware of this diagnostic possibility in cases of mandibular cysts in children— especially when bilateral—to perform the correct treatment, which should not involve the extraction of the affected tooth.
Keywords: Cysts; Jaw Cysts; Odontogenic Cysts